An intervention programme to enhance respectful maternity care in labour by midwives in the public midwives obstetric units in a district in Gauteng - Hanrahan, Barbara Anne (My University, 2021)
Background: Women are experiencing disrespect and abuse in facility-based childbirth in South Africa. Most women utilise the public sector maternity facilities which include Midwives Obstetric Units – midwife-led primary health care facilities. The purpose of this study was to develop an intervention programme which would nurture respectful maternity care in labour by the public midwives in the Midwives Obstetric Units. Methods: A multi-method design using qualitative research methods in three steps, based upon Fraser and Galinsky’s intervention research framework (2010) was used. Forty-six (46) postpartum women were interviewed about their childbirth experience. Forty-five (45) midwives wrote naïve sketches and eighteen (18) midwives participated in three nominal groups. A scoping review looking at respectful maternity care interventions in sub-Saharan Africa, was undertaken, after which the results from all the data sets were collated and an intervention programme developed, using the ADDIE model as a guide. ADDIE is an acronym for analysis, design, development, implementation, and evaluation. The model is useful for planning and development of an intervention programme. The development of the intervention programme was reviewed by an expert group of midwives. Results: Three themes with two sub themes each were identified in the process of the data analysis of the postpartum women’s interviews: midwife actions and personal attributes; women’s expectations and preparation; health systems and resources, and practices. These themes created a template for analysing the midwives’ naïve sketches and nominal groups. Women reported on poor communication and poor interpersonal relationships with the midwives. The midwives reported on the lack of resources (health systems) and work-based stress. An intervention programme addressing malleable factors was developed: A respectful maternity care interpersonal communication training programme, in two parts, for midwives at the Midwives Obstetric Units, was developed to address the research findings. Conclusion: When midwives have poor communication and interpersonal skills, it influences women’s childbirth experiences. When midwives work in incredibly challenging environments with poor resources, it leads to continuous work-based stress which impacts on staff v absenteeism and performance. Debriefing work-based malleable stress and improving interpersonal communication skills are aimed at strengthening midwives working in a challenging environment. The next step is to roll out the intervention programme according to Fraser and Galinsky’s framework, as postdoctoral research, to contribute to nurturing respectful maternity care in labour by midwives in MOUs.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2021